COMPLEX TREATMENT OF SPINAL TUBERCULOSIS IN FUNCTIONAL DISORDERS OF THE GASTROINTESTINAL SYSTEM - Nuriddin N. Tuychiev; Primkul Kh. Nazirov (Central Asian Journal of Medicine, 2022)
Complicated forms of tuberculous spondylitis occur in 70% of adults and 100% of children. Recovery from the disease is recorded in 36.5-69.5% of cases, and disability because of complications of the disease - in 67.0-88.8%. Functional changes in the gastrointestinal tract were detected in 44.0% of patients with complicated spinal tuberculosis. Carrying out therapeutic measures for identified diseases has a positive effect on the effectiveness of surgical treatment. [1,2,3,4,5,6].